Supplying the Roman army on the Pannonian Limes: Amphorae on the territory of Budapest, Hungary (Aquincum and Albertfalva) - Magyar-Hárshegyi, Piroska (Rei Cretariae Romanae Fautorum Acta, 2017)
The aim of this paper, is to give a basic view on the Roman military supply of the capital of Pannonia Inferior, Aquincum and a closely related auxilliary camp at Albertfalva on the basis of nearly 1000 amphorae fragments collected so far. We have mostly indirect data in Pannonia on the regular Roman military supply, the participants involved, and how it was organized. Amphorae findings and their find places therefore have great importance to outline the goods that arrived in masses for the military units, to evaluate their quality and quantity. The amphorae used to transport wine, oil and fishbased products could be considered as proof of the regular military supply. These were part of the Roman military diet (mensa militaris). Amphorae types used to transport olive-, or fruit-based products should be excluded from this category and be studied as complementary supply. It is also important to consider shipments of these goods for the troops not only in relation to times of war versus times of peace or of their regularity, but in relation to the prominent events that needed special provisioning, such as military feasts (e. g. saturnalicium kastrense), anniversaries (e. g. the day of the province, celebrated on the 11th of June), promotions and retiriements.